From cash to central bank digital currencies and cryptocurrencies: A balancing act between modernity and monetary stability - Ansgar Belke; Edoardo Beretta (Research On Money in the Economy (ROME), 2019)
The paper explores the precarious balance between modernizing monetary systems by means of digital currencies (either issued by the central bank itself or independently) and safeguarding financial stability as also ensured by tangible payment (and saving) instruments like paper money. Which aspects of modern payments systems could contribute to improve the way of functioning of today's globalized economy? And, which might even threaten the above mentioned instable equilibrium? This survey-paper aims, precisely, at giving some preliminary answers to a complex - therefore, ongoing - debate at scientific as well as banking and political level.
Keywords: E4; E5; G21; G23; 330; cash; central banks; cryptocurrencies; digital currencies; monetary systems